CHECK UP: A student-designed model for creating innovative patient education materials that your patients will actually use. (September 2021) - Cory, Megan M; Cory, Kevin S; Osmani, Wasif A; Young, Staci; Lundh, Rebecca
Objective: As appointments become more rushed, it is crucial that primary care clinicians consider new and effective ways to provide preventive health education to patients. Currently, patient education is often handouts printed from the electronic medical record system; however, these pieces of paper often do not have the desired impact. Well-established advertising methods reveal that repeated exposure is key in recall and swaying consumer decisions. The Creating Health Education for Constructive Knowledge in Underserved Populations (CHECK UP) Program is a medical student-led program that aims to improve patient recall of health information, health promoting behaviors and health outcomes by applying modified advertising concepts to the delivery of health education. Methods: Patients were given large magnets containing health education information. These patients were interviewed 3–4 months afterwards to assess use and effectiveness of magnets as a means to provide health education. Results: In total, 25 of the 28 patients given CHECK UP magnets agreed to participate. The majority of participants (23/25) kept the magnets and reported that they, as well as others in their households, see the magnets daily. All 23 participants recalled at least 1 health tip from 1 of the magnets. Conclusions: The use of non-traditional materials for patient education allowed for repeated exposure and recall of health information. Consideration for modified use of evidence-based advertising and marketing strategies for the delivery of patient education may be an easy and effective way to provide information to patients outside of the clinical setting and promote health behavioral changes.